Real time detection and characterisation of bioaerosol emissions from wastewater treatment plants - Tian, Jiang-han; Yan, Cheng; Nasir, Zaheer A.; Alcega, Sonia Garcia; Tyrrel, Sean F.; Coulon, Frederic (Elsevier, 2020)
Bioaerosol emissions from wastewater treatment plants may pose adverse health impact on workers and nearby communities. To detect and characterise bioaerosol emissions from wastewater treatment plant (WWTP), a novel real-time bioaerosol sensor, Spectral Intensity Bioaerosol Sensor (SIBS) was employed at a WWTP and a background site. The SIBS records a range of data (size, shape, and fluorescence emission across 16 wavelength bands from 298 to 735 nm for two excitation wavelengths (285 nm and 370 nm)) on single particles in real time. Additionally, excitation-emission matrix (EEM) of wastewater samples obtained by a spectrofluorometer was compared with SIBS spectra from WWTP. The results showed that the average number concentrations of total particles (NT) and fluorescence particles (NF) were both higher at the WWTP (NT = 2.01 cm−3, NF = 1.13 cm−3) than the background site (NT = 1.79 cm−3, NF = 1.01 cm−3). The temporal variation of NF and NT was highly variable at the WWTP and the concentration peaks were consistent with on-site activities. Moreover, the time-resolved number-size distribution of fluorescent particles revealed the predominance of fine scale particles (<1 μm) and the time-series channel by channel number concentrations demonstrated the temporal variability of dominant bio-fluorophores. Furthermore, the overall and size-segregated fluorescence spectra at two sites were multimodal. In particular, the fluorescence intensity increases with increasing particle size in WWTP spectra, which is not present in the background spectra. In addition, the highly resolved SIBS fluorescence spectra were broadly similar to EEM of wastewater. These findings confirmed that the spectrally resolved fluorescence detected by SIBS is capable of providing reliable bio-fluorophores information of bioaerosol emissions generated from wastewater, thus holding the potential for better characterisation of bioaerosols in real time.
Keywords: Bioaerosols; Real-time monitoring; Wastewater treatment plant; Spectral Intensity; Bioaerosol Sensor; Fluorescence spectra